Head injury and risk of Parkinson disease: A systematic review and meta‐analysis. Issue 9 (22nd April 2013) - Jafari, Siavash; Etminan, Mahyar; Aminzadeh, Farhad; Samii, Ali
Abstract Head trauma has been implicated in the etiopathogenesis of Parkinson's disease (PD). We performed a meta‐analysis to investigate the association between head trauma and the risk of developing PD. We included observational studies if they (1) clearly defined PD, (2) defined head trauma leading to concussion, and (3) presented odds ratios (ORs) and 95% confidence intervals (CIs) or provided data to compute these statistics. Random effect model was used to estimate the pooled, adjusted OR. Heterogeneity between studies was evaluated with the Q test and the I2 statistic. We conducted a sensitivity analysis to assess the influence of each study and repeated the analysis by excluding the studies with the largest weights. We used funnel plot to assess the presence of publication bias. After reviewing more than 636 article titles, 34 articles were selected for full review. In total, 22 studies (19 case–control studies, 2 nested case–control studies, and 1 cohort study) were included in the meta‐analysis. The pooled OR for the association of PD and head trauma was 1.57 (95% CI, 1.35–1.83). The results of our meta‐analysis indicate that a history of head trauma that results in concussion is associated with a higher risk of developing PD. © 2013 Movement Disorder Society